2010
DOI: 10.1016/j.apm.2010.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Integration of particle swarm optimization-based fuzzy neural network and artificial neural network for supplier selection

Abstract: a b s t r a c tThis study is intended to develop an intelligent supplier decision support system which is able to consider both the quantitative and qualitative factors. It is composed of (1) the collection of quantitative data such as profit and productivity, (2) a particle swarm optimization (PSO)-based fuzzy neural network (FNN) to derive the rules for qualitative data, and (3) a decision integration model for integrating both the quantitative data and fuzzy knowledge decision to achieve the optimal decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(48 citation statements)
references
References 52 publications
0
48
0
Order By: Relevance
“…First proposed by Kennedy and Eberhart (1995), PSO is initialized with a population of random solutions, which it then searches for optima by updating generations. Then, unlike genetic algorithm, which is based on the survival of fitness, the potential solutions will move through the problem space by following the current optimum particles (Kuo et al 2010b). In more detail, each particle's movement is guided toward its local best known position.…”
Section: Particle Swarm Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…First proposed by Kennedy and Eberhart (1995), PSO is initialized with a population of random solutions, which it then searches for optima by updating generations. Then, unlike genetic algorithm, which is based on the survival of fitness, the potential solutions will move through the problem space by following the current optimum particles (Kuo et al 2010b). In more detail, each particle's movement is guided toward its local best known position.…”
Section: Particle Swarm Optimizationmentioning
confidence: 99%
“…PSO can search a very large space of possible solutions, which makes it very suitable for criteria construction problems in GSCs. In other words, compared to other multi-objective optimization algorithms, such as genetic algorithm, PSO algorithm is a helpful metaheuristic approach which can clearly obtain acceptable solutions (Kuo et al 2010b). On the other hand, the PSO technique is flexible enough to solve the multiple-objective optimization problem, which makes it very suitable for decision-making in partner selection criteria construction.…”
Section: Particle Swarm Optimizationmentioning
confidence: 99%
“…On the AI, Tsai et al [13] developed an approach based on the attribute-based ant colony system (AACS) to construct a platform to examine the critical factors for decision-making in a dynamic business environment in order to select the appropriate suppliers. Kuo et al [14] developed an intelligent supplier decision support system which was able to consider both the quantitative and qualitative factors. It was composed of (1) the collection of quantitative data such as profit and productivity, (2) a particle swarm optimization-(PSO-) based fuzzy neural network (FNN) to derive the rules for qualitative data, and (3) a decision integration model for integrating both the quantitative data and fuzzy knowledge decision to achieve the optimal decision.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The result showed that it can provide better performance compared to the conventional BP neural network. Kuo et al [25] developed an intelligent supplier decision support system which employed a PSO-based fuzzy neural network to derive the rules for qualitative data and build an integration model by taking into account both qualitative and quantitative factors. Gong et al [14] developed a novel PSO algorithm with the tentative reader elimination (TRE) operator to deal with the RFID network planning (RNP) problem.…”
Section: Applications Of Soft Computing Techniques To Indoor Positionmentioning
confidence: 99%